(untitled) (International journal of artificial intelligence, 2026)
We know that cognitive abilities are of great importance for a child to retain all information and learn it perfectly. Cognitive abilities are important for learning and mastering knowledge in mathematics, as well as in other subjects. First, we need to explain what cognitive abilities are, what their characteristics are, and why cognitive abilities are so important in children.